Pierre Loti and André Malraux: irony and tragedy of French writers in Asia (Colloquia Comparativa Litterarum, 2025)
The essay analyses, in the novels Madame Chrysanthème (1887) by Pierre Loti and La Condition humaine (1933) by André Malraux, the strategies of representation and comprehension of cultural Alterity from these French writers, and their effects on the register of the text. In particular, the ironic mode will be distinguished from the tragic mode. In this sense, the difference between the auto-diegetic statute of Lotian narrator, and the polyphony of characters who animate Malraux’s novel has also been underlined.
Keywords: Pierre Loti; André Malraux; irony; tragedy; image of the Other